TIM-3 teams up with PD-1 in cancer immunotherapy: mechanisms and perspectives - Zhuohong Yan; Chunmao Wang; Jinghong Wu; Jinghui Wang; Teng Ma (Molecular Biomedicine)
Abstract Immunotherapy using immune checkpoint inhibitors (ICIs) has become a prominent strategy for cancer treatment over the past ten years. However, the efficacy of ICIs remains limited, with certain cancers exhibiting resistance to these therapeutic approaches. Consequently, several immune checkpoint proteins are presently being thoroughly screened and assessed in both preclinical and clinical studies. Among these candidates, T cell immunoglobulin and mucin-domain containing-3 (TIM-3) is considered a promising target. TIM-3 exhibits multiple immunosuppressive effects on various types of immune cells. Given its differential expression levels at distinct stages of T cell dysfunction in the tumor microenvironment (TME), TIM-3, along with programmed cell death protein 1 (PD-1), serves as indicators of T cell exhaustion. Moreover, it is crucial to carefully evaluate the impact of TIM-3 and PD-1 expression in cancer cells on the efficacy of immunotherapy. To increase the effectiveness of anti-TIM-3 and anti-PD-1 therapies, it is proposed to combine the inhibition of TIM-3, PD-1, and programmed death-ligand 1 (PD-L1). The efficacy of TIM-3 inhibition in conjunction with PD-1/PD-L1 inhibitors is being evaluated in a number of ongoing clinical trials for patients with various cancers. This study systematically investigates the fundamental biology of TIM-3 and PD-1, as well as the detailed mechanisms through which TIM-3 and PD-1/PD-L1 axis contribute to cancer immune evasion. Additionally, this article provides a thorough analysis of ongoing clinical trials evaluating the synergistic effects of combining PD-1/PD-L1 and TIM-3 inhibitors in anti-cancer treatment, along with an overview of the current status of TIM-3 and PD-1 antibodies.